Phenylboronic Acid Derivatives as Validated Leads Active in Clinical Strains Overexpressing KPC‐2: A Step against Bacterial Resistance. (20th February 2018) - Celenza, Giuseppe; Vicario, Mattia; Bellio, Pierangelo; Linciano, Pasquale; Perilli, Mariagrazia; Oliver, Antonio; Blazquez, Jesús; Cendron, Laura; Tondi, Donatella
Abstract: The emergence and dissemination of multidrug resistant (MDR) pathogens resistant to nearly all available antibiotics poses a significant threat in clinical therapy. Among them, Klebsiella pneumoniae clinical isolates overexpressing KPC‐2 carbapenemase are the most worrisome, extending bacterial resistance to last‐resort carbapenems. In this study, we investigate the molecular recognition requirements in the KPC‐2 active site by small phenylboronic acid derivatives. Four new phenylboronic acid derivatives were designed and tested against KPC‐2. For the most active, despite their simple chemical structures, nanomolar affinity was achieved. The new derivatives restored susceptibility to meropenem in clinical strains overexpressing KPC‐2. Moreover, no cytotoxicity was detected in cell‐viability assays, which further validated the designed leads. Two crystallographic binary complexes of the best inhibitors binding KPC‐2 were obtained at high resolution. Kinetic descriptions of slow binding, time‐dependent inhibition, and interaction geometries in KPC‐2 were fully investigated. This study will ultimately lead toward the optimization and development of more‐effective KPC‐2 inhibitors. Abstract : Phenylboronic acid derivatives active against KPC‐2 carbapenemase with nanomolar affinity were designed. These derivatives are able to restore susceptibility to meropenem in clinical strains overexpressing KPC‐2 and are not cytotoxic to human cells. Structures of the best inhibitors in complex with KPC‐2 were obtained. Kinetic descriptions of slow binding, time‐dependent inhibition, and interaction geometries in KPC‐2 were fully investigated.